2008
DOI: 10.1039/b808792j
|View full text |Cite
|
Sign up to set email alerts
|

Solar water-splitting into H2 and O2: design principles of photosystem II and hydrogenases

Abstract: This review aims at presenting the principles of water-oxidation in photosystem II and of hydrogen production by the two major classes of hydrogenases in order to facilitate application for the design of artificial catalysts for solar fuel production. W: Lubitz E: Reijerse J: Messinger W. Lubitz is director of the MPI for Bioinorganic Chemistry and a specialist in advanced EPR techniques. He has a strong interest in both water-splitting and hydrogen production. E. Reijerse is working on hydrogenases using FTIR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
367
0
8

Year Published

2010
2010
2014
2014

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 402 publications
(380 citation statements)
references
References 200 publications
5
367
0
8
Order By: Relevance
“…Potential H 2 ase reactivation was also observed after the exposure to 25% headspace oxygen for 48 h. Photosynthetic organisms were previously reported to display a slow rate of H 2 production owing to the oxygen sensitivity of H 2 ase 20,21 . Thus, the sensitivity of H 2 ase to oxygen has been implicated as a major obstacle to improving phototrophic biological hydrogen production 22 . However, Chader et al 23 showed that Chlorella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Potential H 2 ase reactivation was also observed after the exposure to 25% headspace oxygen for 48 h. Photosynthetic organisms were previously reported to display a slow rate of H 2 production owing to the oxygen sensitivity of H 2 ase 20,21 . Thus, the sensitivity of H 2 ase to oxygen has been implicated as a major obstacle to improving phototrophic biological hydrogen production 22 . However, Chader et al 23 showed that Chlorella sp.…”
Section: Discussionmentioning
confidence: 99%
“…Prominent examples are the only biological catalyst for solar water-splitting, photosystem II, and hydrogenases that reduce protons to molecular hydrogen. [9] A combination of both enzymes leads in principle to a direct solar-to-H 2 conversion via photolytic water-splitting, resulting in molecular oxygen (O 2 ) as by-product. In practice however, this has proven very difficult for many reasons, including enzyme instability and O 2 -sensitivity of many hydrogenases.…”
Section: Biological Approaches To Solar Energy Conversionmentioning
confidence: 99%
“…One of the more successful areas is solar energy related research. This research covers projects involving the synthesis and application of nanomaterials such as carbon nanotubes [16][17][18] ; the production of organic optoelectronic devices [19][20][21] ; synthesis of industrial catalysts [22][23][24] ; fundamental studies on the mechanism of enzymes (such as photosystem II) [9,11,[25][26][27] ; elucidation of the genome sequence, metabolism and biomass formation of various species [28][29][30] ; combustion, gasification and torrefaction of biomass including ash behaviour [31][32][33][34][35][36][37] ; the improvement of biomass (wood) quantity and quality by breeding and genetic modification [38,39] ; and implementation of a biorefinery concept at industrial scale. [40][41][42][43][44][45] For building and maintaining these research facilities and efforts, internal and external funding is required.…”
Section: An Institutional Approach To Solar Energy Conversionmentioning
confidence: 99%
See 2 more Smart Citations